2021
DOI: 10.1371/journal.pone.0253013
|View full text |Cite
|
Sign up to set email alerts
|

The health response to the Rohingya refugee crisis post August 2017: Reflections from two years of health sector coordination in Cox’s Bazar, Bangladesh

Abstract: On August 25 2017, an unprecedented influx of Rohingya refugees began from Rakhine State in Myanmar into Bangladesh’s district of Cox’s Bazar. The scale and acuteness of this humanitarian crisis was unprecedented and unique globally, requiring strong coordination of a multitude of actors. This paper reflects on the health sector coordination from August 2017 to October 2019, focusing on selected achievements and persisting challenges of the health sector strategic advisory group (HSSAG), and the health sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…These findings align with research by Tay et al (2019) and Parmer et al (2019) which both indicated that Rohingya refugees were reluctant to report sexual violence or seek care and showed limited help seeking behaviors, likely due to past restrictions on rights and health care in Myanmar [ 21 , 22 ]. These findings indicate the importance of providing cultural relevant care, potentially outside of traditional medical care delivery pathways, such as through community volunteers or integrated care provision models with other services [ 21 , 23 , 24 ]. Training on screening for CRSV should include skill building on trauma-informed manners of engaging with conflict-affected populations as part of routine medical care [ 25 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings align with research by Tay et al (2019) and Parmer et al (2019) which both indicated that Rohingya refugees were reluctant to report sexual violence or seek care and showed limited help seeking behaviors, likely due to past restrictions on rights and health care in Myanmar [ 21 , 22 ]. These findings indicate the importance of providing cultural relevant care, potentially outside of traditional medical care delivery pathways, such as through community volunteers or integrated care provision models with other services [ 21 , 23 , 24 ]. Training on screening for CRSV should include skill building on trauma-informed manners of engaging with conflict-affected populations as part of routine medical care [ 25 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estimations of increased pregnancy and birth rates shared by our respondents are consistent with published studies and observations by other organizations suggesting birth rates above the historical baseline among Rohingya refugees in Bangladesh [ 20 , 22 , 33 ]. Pregnancy termination was challenging for survivors, given the cultural and religious setting, stigma, underreporting of sexual violence and resulting pregnancy, very limited services for abortion despite some successfully implemented care models with limited reach, extreme complications from unsafe abortions, and legal restrictions [ 24 , 34 , 35 ]. The combination of an increased number of births and the difficulty in accessing safe pregnancy termination would seem to indicate that Rohingya women were sometimes forced to continue pregnancies that were unintended or unwanted.…”
Section: Discussionmentioning
confidence: 99%
“…Guided by the WHO Emergency Response Framework ( 23 ), WHO Bangladesh established an incident management system soon after the largest influx of refugees from Myanmar in 2017 that effectively managed many outbreaks and natural disasters prior to COVID-19 ( 24 , 25 ). Both the WHO incident management system and the ISCG were leveraged for COVID-19, highlighting the benefit of having existing mechanisms using a whole-of society response for emergencies ( 26 ). The COVID-19 response was also extended to the entire population of Cox's Bazar district.…”
Section: Case Study 2: Cox's Bazarmentioning
confidence: 99%
“…31 The importance of involving refugees in delivering health services in humanitarian settings has also been noted in other contexts. 32 In displacement settings, however, researchers ought to recognize how economic and legal factors affect implementers from excluded communities who genuinely commit to the research project but whose contributions are constrained by multiple and competing demands. The Syrian CWs who implemented the Amenah intervention shared the same socioeconomic background and displacement experience as the girls' families.…”
Section: Lessons Learnedmentioning
confidence: 99%